Research on Quantitative Trading of Gold Bitcoin Based on Markowitz Portfolio Theory - Qian Cheng, Rui Wu, Nan Li (Forest Chemicals Review)
Gold has a monetary function since ancient times. Bitcoin, as a bearer currency product, circulates in many countries. Bitcoin, a high-risk asset, will bring higher returns. The stability of gold, a low-risk asset, can resist high risks. How to maximize investors’ profits by combining the stability of gold and the high returns of bitcoin? Based on Markowitz’s portfolio theory, this paper uses Monte Carlo model to obtain the volatility and return of the weighted portfolio such as the optimal risk portfolio and the minimum variance portfolio, and determines the return of the optimal risk portfolio under the maximum sharp ratio. Finally, through the simple moving average method, trend moving average method and yield average method, the prices of gold and bitcoin are predicted by sliding window rolling. Finally, it is found that the cumulative yield of MACD strategy is the highest by using trend moving average method under the optimal risk portfolio, which becomes the best strategy of the highest yield model under the optimal asset portfolio.